Formação continuada de professores no Projeto Escola Cabana: contradições e contrariedades de um processo centrado na escola - Sonia de Jesus Nunes Bertolo (2004)
This research is about the Educator Formation and defines the guidelines on the politics of continued formations from the county of Belém, since Cabanas School Project implementation, that bring to an end of ideals comprehension, proposals and modalities of it. On this approaching, the teachers opinions, anguishes and their analysis of the observations have been put in first place, such as the opinion from the managers (main staff) from the named Project. The official documents from SEMEC and about the teachers continued formation on the educational improvement orbit are also theme and object from the related research. Its the purpose of this High Degree Thesis and its divided in four parts. On the first one, the teachers continued formation on the educational reforms, nowadays, is been argued, searching for a consensus that defines these reforms. Its also about the 90s Brazilian Educational System from the year 1997 until 2003. Secondly, the directives and basics rules from the Cabanas School will be analyzed as a better way to understand the strategies from the policy of the Government of People into the Beléms Municipality Education. At third place, the value of the Educator professional will be discussed, emphasizing their role in the teachers continued formation. At last, this research will show how the formation is seen and how its been thought by a group composed for 26 teachers from SEMEC and by the main staff from the Project. All of this shows how the effort from SEMEC is not enough to break through the old traditional system of teachers formation. There are no matches from the initial purpose to what is seen in the reality in the named School especially about the formation modalities and how SEMEC controls it. This process has created an abyss between the custom proposal and the usual reality practices from the teachers in this Project.